Ekfraza kot izkustvena pripoved - Marinčič, Marko (Ars et humanitas, 2017)
In most interpretations of Virgil's Aeneid inspired by structuralist theory (and by the New Criticism in the anglophone world), the scholarly reader/interpreter sees himself confronted with the text as a self-sufficient cryptic system to be deciphered. As typical examples of "narrative pause", descriptions of works of art are often seen as interpretive clues revealing the deeper meaning of the narrative. Even in cases of ekphrases that are not only focalised by a character, but explicitly narrated through his eyes, the response of the character is often superseded by the zeal of the interpreter in a search for the hidden meanings of what is described. A good example is Aeneas' emotional response to the pictures in Juno's temple at Carthage (1.453-495), which the hero reads as an expression of universal compassion. According to a number of recent interpretations, Aeneas the "ekphrast" is victim of a fatal delusion, as he is unaware of the fact that the temple is dedicated to his enemy Juno, and that the Fall of Troy is represented on the murals as a triumph of the goddess; the real meaning of the depiction is to be revealed in the Punic Wars. Yet those future events are external to the narrative of the Aeneid: except for Dido's prophecy of the birth of the avenger Hannibal, they do not play a role in the narrative. This paper suggests that Aeneas is not only meant to be autonomous as the focaliser of the pictures, but that a number of intratextual links to this ekphrasis later in the poem have a clear psychological logic. The description is mediated through the personal experience of the character, the retrospective narrative in Book 2 reveals the motives for his response to the images, and the meeting with Dido in the Underworld recalls, through a character-focalised citation, Aeneas' experience in front of the pictures in the temple of Juno.
Keywords: ekfraza; Homerus; Lessing, Gotthold Ephraim; naratologija; prvoosebna pripoved; Vergilius Maro, Publius